Building Coalitions: Extra Resources for Coalitions - Elizabeth B. Bolton; Muthusami Kumaran; Lisa Guion (EDIS, 2015)
Organizations join coalitions or collaborations to combine resources in working toward a shared goal. What if additional resources are needed?